DESIGN OF BIOMASS FIRED DRYER USING INTEGRATING DESIGN THINKING AND TRIZ METHOD - Adiyanto, O.; Mohamad, E.; Jaafar, R.; Faishal, M.; Supriyanto, S. (Journal of Advanced Manufacturing Technology (JAMT), 2023)
In the context of Small-Medium Enterprises, the activity of drying wood is still somewhat reliant on solar energy. Drying using solar energy has numerous challenges, one of which is heat fluctuation due to changes in weather. To address this challenge, there is a need for a cost-effective and environmentally-sound dryer. In this paper product design of drying using integration of Design Thinking (DT) and Theory of Inventive Problem Solving (TRIZ) method. The aim from this study is to find out of design of wood dryer based on integration of DT and TRIZ. The results of product design based on integration DT and TRIZ is that the dryer design consists of two main parts, namely the biomass furnace and dryer chamber. The dimensions of the furnace are 80 cm × 90 cm, while the drying racks comprising the enclosure are sized according to the operator. Using anthropometry data, the maximum dimensions of the rack are 196 cm height and 70 cm width. Drying using a biomass dryer is faster than the solar dryer. Drying using a biomass dryer takes seven days to dry the wood to 8% moisture content and takes one day to dry wood to 8% moisture content with a temperature of 150°C.